To the definition of notion «interethnic tolerance» in the process of training of future teachers (Pedagogy of Higher and Secondary Education, 2013)
Tyshyk I. S. To the definition of notion «interethnic tolerance» in the process of training of future teachers.The article reveals theoretical analysis concepts «tolerance» and «ethnic tolerance». Based on the analysis of psycho-pedagogical literature discusses the importance of creating interethnic tolerance as one of the most important factors of professional development for future teachers.
Keywords: tolerance; interethnic tolerance; interethnic interaction; the identity formation of future teacher